Pengaruh Latihan Kekuatan Otot Lengan Terhadap Keterampilan Passing Bawah Pada Permainan Bola Voly Siswa Putra Kelas Atas SDN Maubeli Kabupaten Timor Tengah Utara (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of arm muscle strength training on underarm passing skills in volleyball for upper-grade male students at Maubeli Elementary School, North Central Timor Regency. The study used a quantitative approach with a one-group pretest–posttest design. The population and sample size were 20 students (total sampling). The treatment, arm muscle strength training, was given in a structured manner over five sessions. Data analysis included descriptive statistics, residual normality tests, and simple linear regression. The results showed a correlation coefficient (R) of 0.458 and a determination coefficient (R²) of 0.210, indicating that 21.0% of the variation in underarm passing skills was influenced by arm muscle strength. The ANOVA test showed F count = 4.774 with Sig. = 0.042 (